2018
DOI: 10.3847/1538-4357/aad964
|View full text |Cite
|
Sign up to set email alerts
|

The Remarkable Be+sdOB Binary HD 55606. I. Orbital and Stellar Parameters*

Abstract: Prompted by peculiar spectroscopic variability observed in SDSS/APOGEE H-band spectra, we monitored the Be star HD 55606 using optical spectroscopy and found that it is an exotic double-lined spectroscopic binary (SB2) consisting of a Be star and a hot, compact companion that is probably an OB subdwarf (sdOB) star. Motion of the sdOB star is traced by its impact on the strong He i lines, observed as radial velocity (V r ) variable, double-peaked emission profiles with narrow central absorption cores. Weak He i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…Since sdOB stars are hotter than CBes, their radiation can heat up the outer parts of the CBe disk facing the companion, which can lead to orbital phase-locked spectral features, such as emission in specific spectral lines requiring hotter conditions. CBes for which such behavior was detected include, e.g., o Pup (Koubský et al 2012), HD 161306 (Koubský et al 2014, and HD 55606 (Chojnowski et al 2018), which were all proposed to be Be+sdOB systems. The companions also likely accrete part of the outer disk material, thus forming a secondary accretion disk which can be the origin of high-excitation wind-forming lines (as observed in, e.g., β CMi, Klement et al 2015).…”
Section: Binarity Among Cbesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since sdOB stars are hotter than CBes, their radiation can heat up the outer parts of the CBe disk facing the companion, which can lead to orbital phase-locked spectral features, such as emission in specific spectral lines requiring hotter conditions. CBes for which such behavior was detected include, e.g., o Pup (Koubský et al 2012), HD 161306 (Koubský et al 2014, and HD 55606 (Chojnowski et al 2018), which were all proposed to be Be+sdOB systems. The companions also likely accrete part of the outer disk material, thus forming a secondary accretion disk which can be the origin of high-excitation wind-forming lines (as observed in, e.g., β CMi, Klement et al 2015).…”
Section: Binarity Among Cbesmentioning
confidence: 99%
“…Perhaps the most striking feature of many CBes is the fact that the line emission and circumstellar continuum, and therefore the circumstellar disk, can disappear entirely over the course of months to decades (e.g., π Aqr; Bjorkman et al 2002) or to start growing from scratch (e.g., ω Ori; Sonneborn et al 1988). With the advent of large-scale robotic photometric surveys, these episodes of disk formation and dissipation are now documented by the thousands (e.g., Keller et al 2002;Sabogal et al 2005;Rímulo et al 2018;Labadie-Bartz et al 2018). Some stars show almost periodic or quasi-periodic phases of disk growth and dissipation (e.g., ω CMa; Ghoreyshi et al 2018), but in most of them this seems to happen randomly.…”
Section: Introductionmentioning
confidence: 99%
“…We found that 5 out of 17 are binary stars. Three among them, namely HD 25940 (Wang et al 2018), HD 55606 (Chojnowski et al 2018) and HR 2142 (Schootemeijer et al 2018) have been reported to be binary systems containing a CBe star primary and a sdO (sub dwarf O type) companion. HD 45910 is a known interacting binary system (Koubský et al 2012(Koubský et al , 2011, whereas Cas is also suggested to be a binary system having a possible compact object as a companion (Smith et al 2017).…”
Section: Ca Triplet Line Formation Region: Possibility Of Binaritymentioning
confidence: 99%
“…Another difference from the more traditional Be star is that the emission lines are quite strong and narrow, though this may be due to the small rotational velocity discussed above. Generally they are wider and double-peaked (compare to Figure 1 in Chojnowski et al 2018). However, Be stars are known to be variable on timescales over a few minutes and the emission has even been seen to disappear and reappear over the timescale of decades (Rivinius et al 2013).…”
Section: The First Rsg+be Star Binary Systemmentioning
confidence: 88%